Systematic evaluation of pigment-based whole-cell lead biosensors: challenges in genetic circuit engineering and critical considerations for background noise control - Guo, Yan; Deng, Li-dan; Gong, Wen-wu; Zhang, Juan; Hui, Chang-ye (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionDespite advances in whole-cell biosensors for Pb(II) detection, background leakage and limited dynamic range hinder field deployment. This study systematically evaluates four diverse pbr operons and optimizes genetic circuit architectures to develop high-performance pigment-based Pb(II) biosensors.Methodspbr operons from Cupriavidus metallidurans, Pseudomonas aeruginosa, and Klebsiella pneumoniae were engineered into E. coli TOP10 using decoupled violacein reporter circuits. Five optimization strategies were tested: transcriptional terminators, graded regulator expression (P302-PJ23119 promoters), dual-gene copies, hybrid MerR-PbrR regulators, and circuit architecture variants. All assays used triplicate replicates (n = 3) across 8 time points and 12-15 Pb(II) concentrations.ResultsThe pLVPK-derived pKp-DV construct (PbrR.Kp) achieved optimal performance: LOD of 0.0008 μM, dynamic range 0.0061-50 μM, and high Pb(II) specificity. Transcription terminator insertion further reduced LOD to 0.0002 μM and background noise by 60%. However, regulator dosage and hybrid circuits showed minimal improvement, indicating limited synergistic benefits.DiscussionPbrR.Kp selection and transcriptional insulation are key strategies for reducing leakage. Hybrid circuits require more sophisticated designs. Future work should focus on chromosomal integration and environmental matrix validation to ensure the development of robust, field-ready sensors.